The Visigoths in Gaul and Iberia (update) - Ferreiro, Alberto.
1 online resource.
Keywords: The bibliography includes material published from 2004 to 2006. The historical chronology now includes the fourth century, covering Iberian Fathers such as Gregory of Elvira, Potamius of Lisboa, Prudentius, Pacian of Barcelona and Egeria. Following on from the first bibliography (Brill, 1988) and its first update (Brill 2006) this volume covers recent literature on: Archaeology, Liturgy, Monasticism, Iberian-Gallic Patristics, Paleography, Linguistics, Germanic and Muslim Invasions, and more. In addition, peoples such as the Vandals, Sueves, Basques, Alans and Byzantines are included. The book contains author and subject indexes and is extensively cross-indexed for easy consultation. A periodicals index of hundreds of journals accompanies the volume. Further updates are to be expected at intervals of three years.